Digital Storytelling Training for Senior High School English Teachers - Agustina, Sheila; Megawati, Fika; Zulikhatin Nuroh, Ermawati; Zaki Dzulfikar, Ahmad; Putri Syalwa, Nadliyah (Warta LPM, 2025)
This article reports on a community service program aimed at enhancing English teachers' creativity and digital literacy through the integration of digital storytelling. Conducted in collaboration with MGMP Sidoarjo, the program involved 51 senior high school English teachers who participated in a hands-on workshop using Canva to create digital storytelling materials aligned with their instructional goals. The study employed a mixed-methods approach, combining observation, surveys, and qualitative feedback to evaluate teacher engagement, product quality, and classroom implementation. Findings indicate a notable improvement in teachers' confidence and competence in utilizing digital tools, with all participants successfully producing at least one digital storytelling product. Although time constraints limited full implementation in some classrooms, student responses were overwhelmingly positive, citing increased motivation and engagement due to the visually rich content. Teachers also reflected positively on the training's impact, highlighting its practical value in modernizing English language instruction. The program underscores the importance of supporting teacher development through creative and technology-enhanced pedagogical strategies. It is recommended that schools foster a culture of innovation and that MGMP sustain the momentum through long-term mentoring and experimentation with varied digital learning media in response to evolving educational demands.